Kepemimpinan dalam Krisis: Menilik Kesesuaian Nilai Islam dengan Praktik Kekuasaan di Indonesia - Kencana, Aulia Kiftiah; Wati, Sartina; Syahid, Abdul; Dakir (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The leadership crisis in Indonesia has become an increasingly concerning issue, marked by increasing corruption, weak law enforcement, and declining public welfare. This research uses a qualitative method with a literature approach, reviewing various relevant literature and previous studies. The results of the research on Leadership in Indonesia are currently facing a crisis in the application of the core values of Islamic leadership, such as trust, justice, and social responsibility. Although Islamic teachings emphasize the importance of safeguarding the people's trust and acting fairly, widespread practices of corruption and injustice show that these values are often overlooked. In addition, the neglect of environmental sustainability and the rights of indigenous peoples reflects a lack of social responsibility from leaders, who are more concerned with short-term political and economic interests. Therefore, to achieve effective leadership and integrity, there needs to be a stronger effort to apply Islamic leadership principles in decision-making and resource management, for the welfare of the community and environmental sustainability